1993
DOI: 10.2307/1940477
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Benefits of Stem Curling for Resurrection Plants in the Field

Abstract: The stems of the resurrection plant Selaginella lepidophylla, a poikilohydrous desert pteridophyte, curl dramatically as the plants dry and uncurl when rewetted. We tested the hypothesis that stem curling is a morphological feature that may serve to limit bright-light and/or thermal damage in resurrection plants with a field experiment at a Chihuahuan desert site in west Texas. Experimental plants were irrigated for 3d and then permitted to dry. The plants were either allowed to curl normally or mechanically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…Chlorophyll shading and masking is characteristic of homoiochlorophyllous angiosperm resurrection plants (Farrant et al. , 2003; Sherwin and Farrant, 1998), and frond curling has also been noted in the DT fern Polypodium polypodioides and fern ally Selaginella lepidophylla (Helseth and Fischer, 2005; Lebkuecher and Eickmeier, 1993), features that are thought to minimize photosynthetic ROS production during drying (Farrant, 2000, 2007; Oliver et al. , 1998; Smirnoff, 1993; Vicre et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll shading and masking is characteristic of homoiochlorophyllous angiosperm resurrection plants (Farrant et al. , 2003; Sherwin and Farrant, 1998), and frond curling has also been noted in the DT fern Polypodium polypodioides and fern ally Selaginella lepidophylla (Helseth and Fischer, 2005; Lebkuecher and Eickmeier, 1993), features that are thought to minimize photosynthetic ROS production during drying (Farrant, 2000, 2007; Oliver et al. , 1998; Smirnoff, 1993; Vicre et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is well documented that there are several species of pteridophytes with vegetative DT (Alpert and Oliver, 2002;Gaff, 1977;Helseth and Fischer, 2005;Lebkuecher and Eickmeier, 1993;Muslin and Homann, 1992;Pessin, 1924;Reynolds and Bewley, 1993), little has been reported on the mechanisms used to survive cellular desiccation. It has been inferred by Oliver et al (1998) that as the rate of drying in pteridophytes is slow, they are likely to, like angiosperms, rely more on the de novo accumulation of protection during drying than on the constitutive protection coupled with rehydration-associated repair that is characteristic of bryophytes.…”
Section: Introductionmentioning
confidence: 99%
“…The potential role of leaf movements in avoiding photoinhibition has been discussed for a number of species (e.g. Hirata et al 1983 ; Ludlow & Björkman 1984; Ryel & Beyschlag 1995; stem curling Lebkuecher & Eickmeier 1993). Photoinhibition can reduce carbon gain and thus affect establishment of certain species in special environments ( Ball, Hodges & Laughlin 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Thus there is plenty of evidence of responses of antioxidants and antioxidant enzyme systems to drying and rehydration, but it is hard to discern any consistent general pattern. Lebkuecher & Eickmeier (1991, 1993) and Muslin & Homann (1992) showed that leaf curling in dry Selaginella lepidophylla and Polypodium polypodioides brings clear benefits in limiting photodamage during rehydration in bright light, but their results do not suggest any fundamental differences from nonDT plants. Over all, the evidence suggests that DT plants generally deal with the potential hazards of oxidative damage during the drying–re‐wetting cycle by anticipating the problem at source rather than by invoking extravagantly high activity of antioxidant enzymes or antioxidants after the event.…”
Section: Anatomical and Physiological Requirements And Implicatiomentioning
confidence: 99%